The Usage of International Court of Justice in the Field of Border Delimitation Disputes - Raifovna Shaikhutdinova, Gulnara; Ilgamovich Garaev, Marsel (International Journal of Criminology and Sociology, 2022)
The paper presents the issues of the peaceful settlement of international border disputes on the delimitation of borders in the International Court of Justice. The definition of an international border dispute on the delimitation of borders is being formulated. It is revealed that the legal means of resolving international border disputes developed by the International Court of Justice influenced the development of international law. It is substantiated that for the effective settlement of border disputes on the delimitation of borders, it is necessity to evaluate the interrelation of territorial, ethnic, historical, social and environmental aspects. The tendencies and factors of development of the law enforcement practice of the International Court of Justice in the field of settlement of border disputes are determined.